Partito comunista italiano e "socialismo reale". I casi romeno e polacco - Stefano Santoro (Storicamente, 2013)
From the 1960s to the 1980s, the Italian Communist Party developed new contacts with Eastern Europe: this article considers the Romanian and the Polish cases, which gave a significant contribution in highlighting the increasing distance existing between the Italian communist ideology and its practical implementation in the countries of “real socialism”. After the condemnation of the USSR’s invasion of Czechoslovakia and especially with the beginning of Berlinguer’s secretariat, the Italian Communist Party came as far as to declare the end of the “propulsive drive” of the October Revolution.